Are trajectories of self-regulation abilities from ages 2–3 to 6–7 associated with academic achievement in the early school years? - Sawyer, M; Miller-Lewis, L; Miller-Lewis, L. R.; Lynch, J. W.; Sawyer, M. G.; Mittinty, M; Mittinty, M. N.; Lynch, J; Sawyer, A; Sullivan, T.; Sawyer, A. C. P.; Chittleborough, C (My University, 2014)
Background. The aim of this study was to estimate the association between two key aspects of self-regulation, task attentiveness and emotional regulation assessed from ages 2–3 to 6–7 years, and academic achievement when children were aged 6–7 years. Methods. Participants (n = 3410) were children in the Longitudinal Study of Australian Children. Parents rated children's task attentiveness and emotional regulation abilities when children were aged 2–3, 4–5 and 6–7. Academic achievement was assessed using the Academic Rating Scale completed by teachers. Linear regression models were used to estimate the association between developmental trajectories (i.e. rate of change per year) of task attentiveness and emotional regulation, and academic achievement at 6–7 years. Results. Improvements in task attentiveness between 2–3 and 6–7 years, adjusted for baseline levels of task attentiveness, child and family confounders, and children's receptive vocabulary and non-verbal reasoning skills at age 6–7 were associated with greater teacher-rated literacy [B = 0.05, 95% confidence interval (CI) = 0.04–0.06] and maths achievement (B = 0.04, 95% CI = 0.03–0.06) at 6–7 years. Improvements in emotional regulation, adjusting for baseline levels and covariates, were also associated with better teacher-rated literacy (B = 0.02, 95% CI = 0.01–0.04) but not with maths achievement (B = 0.01, 95% CI = −0.01–0.02) at 6–7 years. For literacy, improvements in task attentiveness had a stronger association with achievement at 6–7 years than improvements in emotional regulation. Conclusions. Our study shows that improved trajectories of task attentiveness from ages 2–3 to 6–7 years are associated with improved literacy and maths achievement during the early school years. Trajectories of improving emotional regulation showed smaller effects on academic outcomes. Results suggest that interventions that improve task attentiveness when children are aged 2–3 to 6–7 years have the potential to improve literacy and maths achievement during the early school years.
Child: Care, Health and Development
Keywords: Children -- Early childhood; Child Development; Child Development -- Emotional; Children -- Outcomes; Childhood and child development; Child Development; Children; Emotional; Early childhood; Outcomes; Childhood and child development